2012
DOI: 10.1007/s12034-012-0305-7
|View full text |Cite
|
Sign up to set email alerts
|

Influence of pH on ZnO nanocrystalline thin films prepared by sol–gel dip coating method

Abstract: ZnO nanocrystalline thin films have been prepared on glass substrates by sol-gel dip coating method. ZnO thin films have been coated at room temperature and at four different pH values of 4, 6, 8 and 10. The X-ray diffraction pattern showed that ZnO nanocrystalline thin films are of hexagonal structure and the grain size was found to be in the range of 25-45 nm. Scanning electron microscopic images show that the surface morphology improves with increase of pH values. TEM analysis reveals formation of ZnO nanoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(20 citation statements)
references
References 15 publications
0
20
0
Order By: Relevance
“…Crystallographic properties of flower‐like ZnO films were investigated by XRD. As shown in Figure , observed all diffraction peaks were confirmed as hexagonal‐structured ZnO without impurity peaks, such as that from hydroxide; these results are in good agreement with those reported in the literature (JCPDS 36‐1451) . A dominant peak, corresponding to (002), is observed at 34.4°, and the peak intensity increased with increasing concentration of NaOH.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Crystallographic properties of flower‐like ZnO films were investigated by XRD. As shown in Figure , observed all diffraction peaks were confirmed as hexagonal‐structured ZnO without impurity peaks, such as that from hydroxide; these results are in good agreement with those reported in the literature (JCPDS 36‐1451) . A dominant peak, corresponding to (002), is observed at 34.4°, and the peak intensity increased with increasing concentration of NaOH.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure 3, observeda ll diffraction peaks were confirmed as hexagonal-structured ZnO without impurity peaks, such as that from hydroxide;t hese results are in good agreement with those reportedi nt he literature (JCPDS 36-1451). [19,20] Ad ominant peak, corresponding to (002), is observed at 34.48,a nd the peak intensity increased with increasing concentration of NaOH. In addition, an increase of the full-width ath alf-maximum( FWHM) value from 0.16 to 0.198 and decrease of the crystallite size from 53.3 to 42.9 nm, as calculated by using the Scherer equation, were also observed with increasing concentration of NaOH.…”
Section: Introductionmentioning
confidence: 99%
“…5. It is commonly noticed in the annealed direct-transition-type semiconductor films [19,20]. Substitution of Ni 2+ ions in tetrahedral sites of the wurtzite structure was also supported by UV-VIS optical spectroscopy.…”
Section: 3optical Propertiesmentioning
confidence: 60%
“…The presence of amine groups increases with pH of the solutions [33]. Thambidurai et al [34] observed a similar effect on sol-gel deposited ZnO thin films. According to this study, when the pH of ZnO solutions increased from 4 to 10, the crystal quality and grain size of ZnO enhanced.…”
Section: Structural Propertiesmentioning
confidence: 77%